STUDENTS-LECTURER(S’) SPEECH ACTS IN THE ACADEMIC PRACTICAL TEACHING SITUATED-COMMUNICATION - Ratna Susanti; Sumarlam Sumarlam; Djatmika Djatmika; Muhammad Rohmadi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to explore the language politeness in an academic situated interaction between student-students and lecturer(s)-students the polytechnic campus environment  mediated by the Javanese cultural background, accurately to describe the reprimand speech acts used as a typical politeness expression; to explain the context following the use of speech acts as a form of politeness in classroom interaction between students and lecturers in academic activities. This study was conducted in Polytechnic Indonusa of Surakarta, Indonesia.The results show that the language used by the lecture and students in communicating are considered polite where the amount of politeness maxims application is much higher when compared to the violation of the maxims. Another result is the level of politeness of students with Javanese cultural background is covering tatakrama and andhapasor.